2021
DOI: 10.14692/jfi.17.1.9-18
|View full text |Cite
|
Sign up to set email alerts
|

Metode single image-NDVI untuk deteksi dini gejala mosaik pada Capsicum annuum

Abstract: Single image-NDVI method for early detection of mosaic symptoms in Capsicum annuum Mosaics are a symptom of a disease often found in red chilies (Capsicum annuum) and is generally caused by viral infections such as the Tobacco mosaic virus. Severe infection can cause stunting and significant yield loss. Serological and molecular detection is a common detection method for plant viruses although they are time-consuming, relatively inefficient for large samples, and are destructive to plants. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…NDVI serves as a valuable tool for estimating the size of plant area experiencing health problems. This method has proven useful for early disease detection and assessment of plant disease severity (Hasan et al 2021;Taufik et al 2023a,b). However, in this study, it is crucial to acknowledge the limitations of NDVI in precisely identifying factors disrupting plant health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDVI serves as a valuable tool for estimating the size of plant area experiencing health problems. This method has proven useful for early disease detection and assessment of plant disease severity (Hasan et al 2021;Taufik et al 2023a,b). However, in this study, it is crucial to acknowledge the limitations of NDVI in precisely identifying factors disrupting plant health.…”
Section: Discussionmentioning
confidence: 99%
“…Rice field images were recorded based on the methodology by Hasan et al (2021) with slight modifications. Recordings were taken from 09:00 am UTC+8 under clear sky conditions, using Canon EOS 750D camera with a lens featuring an On-Lens IR-Ultra Blue filter (www.spencercamera.com).…”
Section: Ndvi Vegetation Indexmentioning
confidence: 99%
“…Two ROIs for each image with dimensions of 180 × 180 pixels each, the total ROI for each symptom variation group is 6 ROIs (ROI focused on the leaf area of the plant image). Furthermore, each ROI image is converted to NDVI image using the Photo Monitoring plugin [13] as in previous studies [10]. 2.3.3.…”
Section: Rgb Image (With Lens Filter) Conversion To Ndvi Imagementioning
confidence: 99%
“…One method for assessing the severity of disease symptoms caused by viruses in chili plants based on digital image processing that is worth trying is NDVI image processing (normalize difference vegetation index). The NDVI method has been reported to be able to distinguish chili IOP Publishing doi:10.1088/1755-1315/1182/1/012004 2 plants infected with Tobacco mosaic virus (TMV) from healthy chili plants and nutrient-deficient chili plants before visual symptoms become visible [10]. However, the magnitude of the NDVI value in each variation of Geminivirus symptoms in chili plants has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Camera sensors with the ability to record changes in leaf spectral reflectance due to disease infection can be used as a non-destructive method for the early detection of plant diseases (Cordon, Andrade, Barbara, & Romero, 2022;Kuska et al, 2022;Nguyen et al, 2021). Hasan, Widodo, Mutaqin, Taufik, & Hidayat (2021) reported that using cameras and digital image analysis techniques, namely SI-NDVI (Single Image-Normalized Difference Vegetation Index), diseased plants can be recognized at 13 days before the symptoms are visible. Furthermore, Dey, Sharma, & Meshram (2016) explained that digital image analysis techniques based on trichromatic colors, namely red, green, and blue (RGB), can be used to measure leaf chlorophyll as an important indicator of plant health index.…”
Section: Introductionmentioning
confidence: 99%